ANALISIS PENGGUNAAN SISTEM INFORMASI AKUNTANSI MANAJEMEN DALAM PERENCANAAN, PENGENDALIAN DAN PENGAMBILAN KEPUTUSAN PADA ARAYAH MADANI GROUP - Jurjais, Andi Andika; Su’un, Muh.; Hajering, Hajering (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
Information including important things for making decisions. Processing and utilization of data will be maximized if it is assisted by a management accounting information system. The purpose of this study is to analyze the use of management accounting information systems in planning, controlling and making decisions at Arayah Madani Group. This type is qualitative using an interpretive paradigm approach. The informants who are the source of the data are the head of the marketing CR division, the head of the finance accounting division and the head of the purchasing warehouse division. The research results obtained: 1) Arayah Madani Group uses a management accounting information system in the form of the Acccurate application which functions to process transaction information in accordance with PSAK, 2) planning at Arayah Madani Group is made according to division requirements and submitted by the Manager to the Board of Directors for later approval, 3) Control and Decision making starts from the manager submitting the planning to the directors and the final decision awaits the decision of the board of directors.